2022
DOI: 10.23887/jjpgsd.v10i1.46320
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia Interaktif Berbasis Problem Based Learning Pada Muatan Matematika Kelas IV SD

Abstract: Penggunaan media pembelajaran dan pemilihan model pembelajaran yang digunakan pada proses pembelajaran kurang bervariasi, khususnya pada muatan matematika. Hal tersebut mengakibatkan pemahaman konsep matematika sebagian siswa masih rendah. Penelitian ini bertujuan untuk menciptakan multimedia interaktif berbasis model Problem Based Learning pada muatan matematika kelas IV SD. Penelitian pengembangan ini menggunakan model pengembangan ADDIE. Metode pengumpulan data yang digunakan adalah metode angket/kuesioner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
0
12
0
3
Order By: Relevance
“…Then, other relevant studies showed that the media developed was suitable for use in learning activities because it had several advantages, namely being interesting, easy to store and easy to apply, and very effective in increasing students' interest in learning. Apart from that, the media presented is easy to remember, can train students' imaginative powers and stimulate students' interest and motivation to learn (Santoso, 2022;Saragi et al, 2021;Wedayanti & Wiarta, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Then, other relevant studies showed that the media developed was suitable for use in learning activities because it had several advantages, namely being interesting, easy to store and easy to apply, and very effective in increasing students' interest in learning. Apart from that, the media presented is easy to remember, can train students' imaginative powers and stimulate students' interest and motivation to learn (Santoso, 2022;Saragi et al, 2021;Wedayanti & Wiarta, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, learning media supports the explanations given by the teacher, attracts and directs students' attention to follow the learning, and increases students' interest and motivation in learning (Trust & Pektas, 2018;Utami & Abdulah, 2020). One component that needs attention in learning planning is selecting appropriate and suitable media for the material being taught and attracting students' interest in learning (Moto, 2019;Wedayanti & Wiarta, 2022). Learning videos are one of the audio-visual media that can improve student learning outcomes; through video shows, students can be stimulated both from a visual perspective through the displays presented and from an audio perspective through accompanying sound.…”
Section: Discussionmentioning
confidence: 99%
“…Temuan penelitian sebelumnya juga menyatakan bahwa E-Book interaktif dapat memudahkan siswa dalam belajar dimanapun (Sari & Airlanda, 2022;Wedayanti & Wiarta, 2022). Temuan penelitian lainnya juga menyatakan bahwa Problem Based Learning dapat meningkatkan berpikir kritis pada siswa (Mella et al, 2022;Wedayanti & Wiarta, 2022).…”
Section: Pendahuluanunclassified
“…Temuan penelitian sebelumnya juga menyatakan bahwa E-Book interaktif dapat memudahkan siswa dalam belajar dimanapun (Sari & Airlanda, 2022;Wedayanti & Wiarta, 2022). Temuan penelitian lainnya juga menyatakan bahwa Problem Based Learning dapat meningkatkan berpikir kritis pada siswa (Mella et al, 2022;Wedayanti & Wiarta, 2022). Berdasarkan beberapa penelitian tersebut dapat dikatakan bahwa pengembangan E-Book interaktif berbasis Problem Based Learning dapat meningkatkan keaktifan dan berpikir kritis pada siswa.…”
Section: Pendahuluanunclassified